Riconoscimento di rombi (Psetta maxima) pescati e allevati mediante analisi degli acidi grassi e degli isotopi stabili - M.L. Busetto; V.M. Moretti; F. Caprino; I. Giani; F. Bellagamba; J. M. Moreno Rojas; C. Guillou (2008)
The aim of the present work was to study the potential application of fatty acid analysis and IRMS (Isotope Ratio Mass Spectrometry) of carbon and nitrogen in the muscle tissue of wild and farmed turbot to discriminate the production method and the geographical origin of fish. The results showed that the combination of fatty acids and isotopic measurements is a promising method to discriminate between wild and farmed fish and between wild fish of different geographical origin. In particular, IRMS alone did not permit us to separate completely farmed from wild samples resulting in some overlaps between Danish wild and Spanish farmed turbot. On the other hand, fatty acids alone differentiated between farmed and wild samples by linoleic acid (18:2n-6) but were not able to distinguish between the two groups of wild turbot.